Thermo‐mechanical evaluation of novel composite propellant formulations based on styrene‐ethylene/butylene‐styrene block copolymer - Wilkinson, Peter J.; Kister, Guillaume; Gill, Philip P. (Wiley, 2025)
Two novel composite propellant formulations have previously been produced from a binder consisting of the thermoplastic elastomer styrene‐ethylene/butylene‐styrene (SEBS) and a solid filler, either ammonium perchlorate (AP) or 1,3,5‐trinitro‐1,3,5‐triazinane (RDX). The binder, being a commercially available off‐the‐shelf polymer, has many advantages over a typical bespoke binder, particularly cost and risk of obsolescence. The thermal and hazard properties have shown potential for these formulations. This paper addresses the mechanical properties over a range of service and storage temperatures, which is important in the safety and durability of a propellant. The glass transition temperatures, as determined by dynamic mechanical analysis (DMA), were found to be influenced by the type of filler and the solids loading. The lower glass transition was seen to increase slightly from −41°C for unfilled SEBS to −39°C (AP/SEB 84/16) with AP as a filler; conversely, it decreased to −45°C (RDX/SEBS 80/20) with RDX. The upper glass transition was found to have decreased from 102°C to around 91°C for all formulations tested. Use of DMA—time temperature superpositioning found that the filler influenced the frequency dependency of the mechanical behaviour. Compared to typical AP composite propellants, both the storage modulus (E’) from DMA and Young's modulus (E) from tensile testing were substantially greater. Tensile testing also showed that the strain at maximum stress (εm) was significantly less. However, the maximum stress (σmax) was similar. SEBS has shown potential as a binder for a stiffer composite propellant (higher modulus).
Keywords: DMA; solid propellant formulations; strain energy density; tensile testing; thermoplastic elastomer; 4004 Chemical Engineering; 40 Engineering; Chemical Physics